PEMANFAATAN TEKNOLOGI INFORMASI DALAM MANAJEMEN PENGETAHUAN BAGI PELAKU USAHA KECIL MENENGAH DI KOTA BATAM - Adam, Steffi (JURSIMA, 2018)
The purpose of this study is to determine the used of knowledge management methods for SMEs entrepreneurs by using information technology. SMEs as the support and savior of the economy should be able to manage their knowledge, in order to compete in knowledge-based economy era. The existence of information technology (IT) is used as a tool and technique to simplify the process of knowledge management. With the existence of the IT, knowledge management process can be done quickly, effectively and efficiently. This study using descriptive analysis.  The samples of this research are 30 SMEs entrepreneurs of food production (culinary). From the results of the descriptive analysis we can see that Methods and tools of knowledge management involving the most widely used IT SMEs in Batam is an advanced search tools. While knowledge management methods and tools that do not involve IT most used by SMEs in Batam is a Peer Assist. (SA)